KONTRIBUSI KREATIVITAS DAN FASILITAS LABOR TERHADAP HASIL BELAJAR TEKNIK PEMROGRAMAN SISWA KELAS X TEKNIK AUDIO VIDEO SMK NEGERI 1 BUKITTINGGI - Taufik Mardatillah; Titi Sriwahyuni; Dedy Irfan Irfan (Universitas Negeri Padang, 2016)
This study aimed to determine the contribution of creativity and laboratory facilities Against learning outcomes Program Audio and Video (TAV) Class X in SMK Bukittinggi. This study is correlational description. The technique of sample selection in this study using simple random sampling of 36 respondents in SMK Negeri 1 Bukittinggi. The data were analyzed using statistical methods of multiple regression analysis. The results of data analysis showed:1) creativity and laboratory facilities together contribute significantly to the learning outcomes of 25,70%, 2) creativity contribute significantly to the learning outcomes of 16,16% and 3) laboratory facilities contributes significantly to the success of learning outcomes of 13,83%. KeyWord : creativity, laboratory facilities, learning outcomes.